Tradisi Ngesuki Masyarakat Kecamatan Secanggang Dalam Analisis Kaidah Maqashid Alfadz - Iqbal, M; Harahap, Muhammad Rifai (Yayasan Rahmat Islamiyah, 2023)
In Secanggang sub-district, precisely in Suka Mulia Village, Tanjung Mulia Hamlet, there is a unique tradition carried out by the people which they consider as a form of mutual help. This tradition, known as